Tibial Plafond Fractures and the Impact of Social Media Support Groups on Patient Perceptions - Alexandra F. Flaherty; Dana Perim; Annie Waite; Alvarho Guzman; Ernest N. Chisena (Journal of Orthopaedic Experience & Innovation, 2026)
Background Tibial plafond fractures are severe injuries that often result in a prolonged treatment and recovery process, as well as poor outcomes and high complication rates. Given this, an online support group exists for patients to gain support and advice from a community of patients with the same injury. Similar groups exist for other chronic medical conditions and traumatic injuries; such groups have been studied to determine the impact on the affected patients. There have been no prior studies specifically investigating the effect of these support groups on patients with tibial plafond fractures. Purpose The aim of this study is to determine subjectively the impact of a social media support group on patients who sustained a tibial plafond fracture. Methods An anonymous 16-quesiton survey was distributed via an online pilon support group between July 2023 and August 2023. Results Overall, 151 survey responses were collected and included, which resulted in an overall response rate of 7.1% among all members of the support group and 82.9% response rate among the active members. 73.9% of the respondents were female, while 24.8% identified as male and 1.3% identified as other. The majority of respondents were between the ages of 41 and 60 years old. On average patients were 2.95 (2.60) years from their original injury. The majority were treated with a two-stage procedure (61.6%), followed by primary open reduction internal fixation (29.8%), and definitive external-fixation (4.0%). On average respondents underwent 2.83 (1.85) total surgeries. 58.5% of respondents reported that the severity of their injury was not properly explained at the time of injury, and 78.1% reported that membership in the support group changes their perception of their injury prognosis. In terms of return to activity, respondents reported returning to an average of 64% of their pre-injury activity level related to work and 50.8% related to hobbies and recreational activities. Conclusion Tibial plafond fractures are severe injuries that often have poor functional outcomes and can drastically decreased patients’ quality of life post-injury. The online support group changed their perception of their injury, provided a means of seeing patients further along in recovery and for some respondents aided in making medical decisions. Overall, the majority of respondents would recommend the group to other patients with tibial plafond fracture, suggesting the support group had a positive impact on respondents. Level of Evidence Level III